Strategy to Grow Children's Honesty Characters through The Media of Islamic Animated Films at PAUD Firdaus Karanganyar - Sulastri, S; Slamet, Sri (Universitas Muhammadiyah Surakarta, 2023)
This study aims to explore and analyse the strategies employed in nurturing honesty among children through Islamic animated films at PAUD Firdaus Karanganyar. Honesty is a core value in Islam, and instilling this virtue early is crucial for fostering integrity in individuals. The research methodology adopts a qualitative approach involving data collection through observations, interviews, and document analysis. The findings revealed that PAUD Firdaus Karanganyar implements a range of strategies to cultivate honesty characters in children, including carefully selecting Islamic animated films that impart moral lessons about honesty. Moreover, group discussions and role-playing activities effectively reinforce ethical values and encourage children to reflect on the importance of honesty in their daily lives. Additionally, incorporating narratives aligned with Islamic principles plays a significant role in the effectiveness of animated films as a medium for character education. These findings offer valuable insights into the efficacy of using Islamic animated films to promote honesty among children at an early stage of their development. Such initiatives lay a strong foundation for children's moral and ethical growth, shaping their character and guiding their conduct in the future.